LEARNING PREFERENCES BETWEEN BOYS AND GIRLS IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2014)
The study of participative preferences are being increasingly explored (Ruiz, Graupera, Rico and Mata, 2004; Ruiz Moreno Graupera and Rico, 2010), supporting the importance that many of the educators recognize about knowing the preferences of learners and self-perception in learning motor skills (Lintunen, 1999). The aim of the study was to know, understand and compare the participative preferences in the learning of physical education between boys and girls in the primary and secondary education. The aim of the study was to determine and compare participative preferences on the process of learning physical education among students of elementary and secondary education. 561 students from 6 to 18 years old (277 boys and 284 girls) filled out the Graupera/Ruiz Preferences Scale of Social Interaction in PE Learning (GR). This instrument has 28 items divided into four categories: affiliation, competition, cooperation and individualism. The analysis shows how students score higher in boy’s competition category than those done by girls. Data analysis shows how male students score higher in the factor of competitiveness versus the values presented by female students. The differences regarding the sex appear in numerous investigations showing how the girls are less competitive than the boys coinciding with Ruiz, Graupera, Moreno and Rico’s research (2010)
Keywords: social interaction; learning preferences; affiliation; competition; gender